The Influence of Promotion and Brand Image on Customer Purchase Decision at PT Isuindomas Putra, Medan - Alfonsius; Crystal (Fakultas Ekonomi Dan Bisnis Universitas Pelita Harapan, 2022)
This research is conducted in order to analyze the influence of promotion and brand image on customer purchase decision of Isuzu truck at PT Isuindomas Putra, Medan. The company faces some problems in terms of promotion and brand image. This research is conducted by using quantitative method by distributing the questionnaire to 97 respondents who have ever bought Isuzu truck at PT Isuindomas Putra, Medan. In order to determine the amount of the sample for this research, the writer uses Lemeshow formula. The writer also uses non probability sampling with the convenience or accidental sampling as the sampling technique. In terms of data analysis method, the writer uses multiple linear regression. The result of the t – test partial hypothesis is the promotion has positive and significant partial influence on customer purchase decision of Isuzu truck at PT Isuindomas Putra, Medan and the brand image also has positive and significant partial influence on customer purchase decision of Isuzu truck at PT Isuindomas Putra, Medan. The result of the F – test simultaneous hypothesis is the promotion and brand image have simultaneous influence on customer purchase decision of Isuzu truck at PT Isuindomas Putra, Medan. The result in this research also shows that brand image has the most dominant influence on customer purchase decision.